1999
DOI: 10.1182/blood.v93.2.599.402k06_599_606
|View full text |Cite
|
Sign up to set email alerts
|

P-Glycoprotein Expression on Normal and Abnormally Expanded Natural Killer Cells and Inhibition of P-Glycoprotein Function by Cyclosporin A and Its Analogue, PSC833

Abstract: P-glycoprotein (P-gp), a transmembrane efflux pump encoded by theMDR1 gene, has been found to be expressed in many normal bone marrow and peripheral blood cells. Among normal leukocytes, CD3−CD16+ or CD3−CD56+ lymphocytes, ie, natural killer (NK) cells, express relatively high levels of P-gp, but little is known about P-gp in abnormally expanded NK cells. In this study, we examined the expression and activity of P-gp on NK cells derived from three normal donors, six patients with indolent NK cell-lineage granu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 35 publications
1
59
1
Order By: Relevance
“…Nasal NK-cell lymphoma, especially of advanced stage, has a poor prognosis with resistance to various antitumor agents (Isobe et al, 2004;Oshimi, 2007;Suzuki et al, 2008). Although high expression of p-gp has been reported in the disease, other molecular mechanism of the chemo-resistance is largely unknown (Egashira et al, 1999). In this study, we revealed that STAT3 is activated in considerable portion of nasal NK-cell lymphoma, and activation of STAT3 is correlated with Mcl-1 expression.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Nasal NK-cell lymphoma, especially of advanced stage, has a poor prognosis with resistance to various antitumor agents (Isobe et al, 2004;Oshimi, 2007;Suzuki et al, 2008). Although high expression of p-gp has been reported in the disease, other molecular mechanism of the chemo-resistance is largely unknown (Egashira et al, 1999). In this study, we revealed that STAT3 is activated in considerable portion of nasal NK-cell lymphoma, and activation of STAT3 is correlated with Mcl-1 expression.…”
Section: Discussionmentioning
confidence: 62%
“…Although initially localized to the nose and sinuses, the disease rapidly disseminates to various sites and has a poor prognosis. A high expression level of p-glycoprotein (p-gp) renders this disorder resistant to various antitumor agents (Egashira et al, 1999).…”
Section: S U M M a R Ymentioning
confidence: 99%
“…The disease is refractory to chemotherapy and exhibits a relentless progressive course with a poor outcome. As in extranodal NK/T-cell lymphoma, this poor outcome may be partially explained by the presence of P-glycoprotein (P-gp), a multidrug resistance gene-encoded protein on the cell membrane, that extrudes various cytotoxic agents, such as vinca alkaloids and anthracyclines (Yamamoto et al, 1993;Yamaguchi et al, 1995;Egashira et al, 1999), and combination chemotherapies using P-gp-unrelated drugs are to be expected. Allogeneic haematopoietic stem cell transplantation (HSCT) has been tried with only a few successful cases being reported.…”
Section: Treatmentmentioning
confidence: 99%
“…(P-gp), which extrudes various cytotoxic agents, may contribute to their refractoriness to various anti-cancer agents (Yamamoto et al, 1993;Yamaguchi et al, 1995;Egashira et al, 1999). Some reports have recently shown that l-asparaginase, a commonly used agent for childhood acute lymphoblastic leukaemia (ALL), is effective against refractory and relapsed cases of NK-cell lymphoma (Matsumoto et al, 2003;Yong et al, 2003).…”
mentioning
confidence: 99%